Hexagonal boron nitride loaded silver nanoparticle hybrid filler, ANF composite material and preparation method

By modifying hexagonal boron nitride and reducing silver nanoparticles in situ, the problems of uneven distribution of silver nanoparticles and harsh reaction conditions in the prior art are solved, an efficient and environmentally friendly preparation process is achieved, and the thermal conductivity and mechanical properties of the composite material are improved.

CN120137267APending Publication Date: 2025-06-13SHANGHAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510508586.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

In the prior art, the hybrid filler of hexagonal boron nitride-loaded silver nanoparticle is prone to shedding and agglomeration due to the weak combination of elemental silver and hexagonal boron nitride, and the reaction rate of using strong reducing agents is too fast, resulting in difficult control of the morphology of the nanoparticles, and the reaction conditions are harsh, high costs, and easy to cause pollution to the environment.

Method used

By modifying hexagonal boron nitride with organic substances containing catechol groups, and using polyvinylpyrrolidone as a protective agent, silver nanoparticles are loaded on the surface of hexagonal boron nitride by reducing silver nitrate in situ, avoiding the need for strong reducing agents.

Benefits of technology

The uniform distribution and size control of silver nanoparticles is achieved, the preparation cost is reduced, the process flow is simplified, and the environment is friendly, suitable for large-scale production. At the same time, the thermal conductivity and mechanical properties of aramid nanofiber composite materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120137267A_ABST
    Figure CN120137267A_ABST
Patent Text Reader

Abstract

The invention relates to a hexagonal boron nitride loaded silver nanoparticle hybrid filler, an ANF composite material and a preparation method, and the preparation method of the hybrid filler comprises the following steps: modifying hexagonal boron nitride by using an organic matter containing catechol groups, and reducing silver nitrate in situ by using polyvinylpyrrolidone as a protective agent to obtain the hexagonal boron nitride loaded silver nanoparticle hybrid filler. Loading the silver nanoparticles on the surface of the hexagonal boron nitride to obtain the hexagonal boron nitride loaded silver nanoparticle hybrid filler; in the preparation process, a strong reducing agent does not need to be additionally used, silver ions can be reduced into silver nanoparticles through catechol groups, meanwhile, o-benzoquinone is generated to adsorb the silver nanoparticles, aggregation of elemental silver can be effectively prevented, and the size and distribution of the silver nanoparticles can be controlled; meanwhile, according to the aramid nanofiber composite material added with the filler, the filler and a matrix can generate good interfacial compatibility, so that a relatively effective heat conduction path is formed, and the heat conduction and mechanical properties of the aramid nanofiber composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of aramid nanofiber composite materials, and particularly relates to a hexagonal boron nitride supported silver nanoparticle hybrid filler, an aramid nanofiber composite material and a preparation method thereof. Background Art

[0002] With the advent of the 5G era, electronic products have been continuously miniaturized, high-frequencyized and integrated, which has led to a large amount of heat accumulating in a small area, causing the working temperature of electronic devices to rise, thereby having an adverse impact on their stability, working reliability and service life. Traditional heat dissipation methods are not sufficient to meet the current diversified heat dissipation requirements. How to transfer this heat has urgently become the research focus of preparing high thermal conductivity materials. However, the performance requirements of thermal conductivity materials not only consider thermal conductivity, but also need to comprehensively consider various characteristics such as chemical stability, mechanical strength and electrical insulation performance. Therefore, polymer-based thermal conductivity materials have attracted much attention.

[0003] Aramid nanofiber (abbreviated as ANF) is a poly(p-phenyleneterephthalamide) (PPTA) fiber with a diameter between 1 and 100 nm. Compared with macroscopic para-aramid nanofibers, aramid nanofibers have a larger specific surface area and aspect ratio, and have excellent properties such as high strength, high modulus, good insulation and high temperature resistance, and can be used as an excellent polymer matrix.

[0004] Hexagonal boron nitride (h-BN) is a ceramic material with a graphite-like structure, and has excellent properties such as high thermal conductivity, good electrical insulation performance and high temperature resistance, and can be used as a performance excellent thermal conductivity filler to prepare high thermal conductivity and electrically insulating polymer composites.

[0005] It has been found that compounding hexagonal boron nitride with aramid nanofibers can improve the thermal conductivity of aramid nanofiber composites. However, due to the chemical inertness of the surface of hexagonal boron nitride, it has a poor combination with the aramid nanofiber matrix, and it is difficult to form an effective thermal conduction path in the matrix, making it difficult to improve the thermal conductivity of aramid nanofiber composites. Usually, it is necessary to perform surface modification on hexagonal boron nitride to improve its dispersion in the matrix, and further modify it into a hybrid filler to form a more effective thermal conduction path.

[0006] At present, for the preparation of the hybrid filler of silver nanoparticles supported on hexagonal boron nitride, silver ions are mainly adsorbed on the surface of hexagonal boron nitride, and strong reducing agents such as hydrazine hydrate, sodium borohydride and formaldehyde are added externally to reduce the silver ions to obtain silver nanoparticles. Due to the surface inertness of hexagonal boron nitride, the surface of hexagonal boron nitride needs to be modified before so that silver ions can be better adsorbed on its surface. In the process of loading silver nanoparticles on the surface of hexagonal boron nitride by this method, on the one hand, the elemental silver obtained by reduction has a weak binding with hexagonal boron nitride, is easy to fall off and agglomerate, resulting in uneven distribution of silver nanoparticles on hexagonal boron nitride. On the other hand, when strong reducing agents such as sodium borohydride and hydrazine hydrate reduce silver nanoparticles, although the reaction rate is fast and the yield is high, the too fast reaction rate will make it difficult to control the morphology of the nanoparticles, the nanoparticles have poor size uniformity, and are easy to form agglomerates; on the third hand, when using such strong reducing agents, the reaction conditions are harsh, the cost is high, and it is easy to cause environmental pollution, which does not conform to the concept of green methods. Summary of the Invention

[0007] In view of this, the present disclosure provides a hybrid filler of silver nanoparticles supported on hexagonal boron nitride, an aramid nanofiber composite material and a preparation method thereof, which solve the problems that in the hybrid filler of silver nanoparticles supported on hexagonal boron nitride, due to the weak binding between elemental silver and hexagonal boron nitride, it is easy to fall off and agglomerate, resulting in uneven distribution of silver nanoparticles on hexagonal boron nitride, and the too fast reaction rate of strong reducing agents will make it difficult to control the morphology of nanoparticles, the silver nanoparticles have poor size uniformity, and the reaction conditions are harsh, the cost is high, and it is easy to cause environmental pollution.

[0008] To achieve the above invention purpose, on the first aspect, the preparation method of the hybrid filler of silver nanoparticles supported on hexagonal boron nitride provided by the present disclosure includes:

[0009] After modifying hexagonal boron nitride with an organic substance containing catechol groups, using polyvinylpyrrolidone as a protective agent, in-situ reducing silver nitrate to load silver nanoparticles on the surface of hexagonal boron nitride, thereby obtaining the hybrid filler of silver nanoparticles supported on hexagonal boron nitride.

[0010] Preferably, the method of using an organic substance containing catechol groups to modify hexagonal boron nitride, using polyvinylpyrrolidone as a protective agent, and reducing silver nitrate to load silver nanoparticles on the surface of hexagonal boron nitride to obtain the hybrid filler of silver nanoparticles supported on hexagonal boron nitride includes:

[0011] An organic compound containing a catechol group is used as a modifier. After subjecting hexagonal boron nitride to liquid-phase ball milling with an aqueous solution of the modifier, the modified hexagonal boron nitride obtained by centrifugal separation is redispersed in deionized water to prepare an aqueous solution of modified hexagonal boron nitride. After continuously adding polyvinylpyrrolidone and dispersing it evenly by ultrasonic treatment, it reacts with a silver nitrate solution under the conditions of magnetic stirring and heating, and a mixed solution is obtained by in-situ reduction. After cooling to room temperature, the mixed solution is centrifuged and vacuum dried to obtain the hexagonal boron nitride-supported silver nanoparticle hybrid filler.

[0012] Preferably, the concentration of the aqueous solution of the modifier is 20 - 50 mg / mL, and the dispersion concentration of hexagonal boron nitride powder in the aqueous solution of the modifier is 16.67 - 33.33 mg / mL.

[0013] Preferably, the mass ratio of modified hexagonal boron nitride to silver nitrate is 4 - 20:1.

[0014] In a second aspect, the aramid nanofiber composite material provided by the present disclosure includes:

[0015] The hexagonal boron nitride-supported silver nanoparticle hybrid filler according to any one of the first aspect.

[0016] Preferably, the hexagonal boron nitride-supported silver nanoparticle hybrid filler accounts for 40 - 50 wt% of the total mass of the aramid nanofiber composite material.

[0017] In a third aspect, a method for preparing the aramid nanofiber composite material according to the second aspect includes:

[0018] Disperse aramid nanofibers in a dimethyl sulfoxide solution of potassium hydroxide to obtain an aramid nanofiber / dimethyl sulfoxide dispersion, and disperse the aramid nanofiber / dimethyl sulfoxide dispersion in deionized water to obtain an aramid nanofiber dispersion;

[0019] Mix the prepared deionized water dispersion of the hexagonal boron nitride-supported silver nanoparticle hybrid filler with the aramid nanofiber dispersion to obtain a mixed system;

[0020] Use the wet papermaking method to subject the mixed system to aqueous-phase physical blending, vacuum-assisted filtration, and vacuum drying treatments to prepare the aramid nanofiber composite material.

[0021] Preferably, the mass ratio of aramid nanofibers to potassium hydroxide is 1:0.5 - 2.5; the concentration of potassium hydroxide in the dimethyl sulfoxide solution of potassium hydroxide is 1 - 5 g / L, and the volume ratio of dimethyl sulfoxide to deionized water is 10 - 50:1.

[0022] Preferably, the dispersion of aramid nanofibers in a dimethyl sulfoxide solution of potassium hydroxide is carried out by stirring at a stirring temperature of 20-30°C, a stirring rate of 500-800 r / min, and a time of 2-8 h.

[0023] Preferably, the concentration of the deionized water dispersion of the hexagonal boron nitride supported silver nanoparticle hybrid filler is 0.4-0.5 mg / mL.

[0024] Preferably, the force of the vacuum-assisted filtration is 0.5-0.8 MPa; the temperature of the vacuum drying is 50-80°C, and the time is 8-16 h.

[0025] The beneficial effects of the present invention are as follows:

[0026] 1. For the hexagonal boron nitride supported silver nanoparticle hybrid filler of the present invention, its preparation method does not require the additional addition of strong reducing agents such as hydrazine hydrate and sodium borohydride. The catechol group in the modifier can reduce silver ions into silver nanoparticles, and at the same time generate o-benzoquinone to adsorb silver nanoparticles, preventing the aggregation of elemental silver and controlling the size and distribution of silver nanoparticles. Moreover, the preparation process is simple, the reaction conditions are mild, the cost is low, and it is environmentally friendly, suitable for large-scale production, and can be widely used as a thermal conductive material.

[0027] 2. For the hexagonal boron nitride supported silver nanoparticle hybrid filler / aramid nanofiber composite of the present invention, during the aramid nanofiber forming process, silver at the nanoscale connects hexagonal boron nitride, reducing the interfacial thermal resistance between hexagonal boron nitrides. The modifier improves the dispersion of the hybrid filler in the aramid nanofiber matrix, so that the hybrid filler can be evenly distributed in the matrix, and the interfacial compatibility between the filler and the matrix is good, forming a relatively effective thermal conductive path, thereby improving the thermal conductivity and mechanical properties of the aramid nanofiber composite. Description of the Drawings

[0028] The drawings herein are incorporated into the specification and form a part of this specification. These drawings show embodiments in line with the present disclosure and are used together with the specification to explain the technical solutions of the present disclosure.

[0029] Figure 1 are the infrared spectra of the original hexagonal boron nitride (h-BN), tannic acid modified hexagonal boron nitride (f-h-BN-1) prepared in Example 1, gallic acid modified hexagonal boron nitride (f-h-BN-2) prepared in Example 7, and hexagonal boron nitride supported silver nanoparticle hybrid fillers (h-BN@AgNPs-1) prepared in Example 1 and (h-BN@AgNPs-2) prepared in Example 7;

[0030] Figure 2SEM images of the hybrid filler of silver nanoparticles supported on hexagonal boron nitride prepared in Example 1 (Figure A), Example 2 (Figure B), Example 3 (Figure C), and Example 7 (Figure D) (the circled parts in the figures are silver nanoparticles with uniform particle size and uniform distribution).

[0031] Figure 3 Partial detachment of silver nanoparticles on the hybrid filler of silver nanoparticles supported on hexagonal boron nitride prepared using a strong reducing agent (Figure A) and the hybrid filler of silver nanoparticles supported on hexagonal boron nitride prepared using a strong reducing agent (Figure B) prepared in Comparative Example 5. Detailed implementation manners

[0032] To enable those skilled in the art to better understand the technical solutions in the present invention, the following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0033] To solve the problems in the background art, the preparation idea of the hybrid filler of silver nanoparticles supported on hexagonal boron nitride in the present invention is as follows:

[0034] Improve hexagonal boron nitride using an organic substance containing catechol groups, and then use the modified hexagonal boron nitride as a reducing agent, assisted by the protective agent polyvinylpyrrolidone to reduce silver nitrate, so that silver nanoparticles are successfully loaded on the surface of hexagonal boron nitride, thus completing the process of successfully preparing the hybrid filler of silver nanoparticles supported on hexagonal boron nitride without the need to additionally use a strong reducing agent.

[0035] In the embodiments of the present disclosure, the preparation method of the hybrid filler of silver nanoparticles supported on hexagonal boron nitride is as follows:

[0036] Perform liquid-phase ball milling on hexagonal boron nitride using a modifier aqueous solution, centrifuge and separate to obtain modified hexagonal boron nitride, then re-ultrasonically disperse it in deionized water to obtain a modified hexagonal boron nitride aqueous solution. Continue to add polyvinylpyrrolidone and ultrasonically disperse it evenly, and then react with a silver nitrate solution under the conditions of magnetic stirring and heating to in-situ reduce to obtain a mixed solution. After cooling to room temperature, perform centrifugation and vacuum drying on the mixed solution to obtain the hybrid filler of silver nanoparticles supported on hexagonal boron nitride.

[0037] In various embodiments of the present disclosure, the modifier is an organic compound containing a catechol group; the organic compound containing a catechol group performs non-covalent surface modification on h-BN through π-π interaction, improves the dispersibility of h-BN, and reduces silver ions through the catechol group in the modifier to in-situ grow silver nanoparticles on the surface of hexagonal boron nitride, without the need to additionally add a strong reducing agent (such as sodium borohydride, etc.), avoiding the agglomeration of silver nanoparticles. The entire preparation process is simple and the cost is low, meeting the concept of green manufacturing. Preferably, the organic compound containing a catechol group is one of tannic acid or gallic acid.

[0038] In various embodiments of the present disclosure, preferably, the concentration of the modifier aqueous solution is 20 - 50 mg / mL, and the dispersion concentration of hexagonal boron nitride powder in the modifier aqueous solution is 16.67 - 33.33 mg / mL; preferably, the ball milling speed is 300 - 500 rpm and the time is 8 - 16 h; preferably, the material of the ball milling tank used in the liquid-phase ball milling process is corundum, and the material of the grinding beads is zirconia; the grinding beads are a mixture of two kinds of grinding beads with diameters of 5 mm and 10 mm (mass ratio of 1:1); the mass ratio of the grinding beads to hexagonal boron nitride is 200 - 400:1.

[0039] In various embodiments of the present disclosure, preferably, the mass ratio of the modified hexagonal boron nitride to polyvinylpyrrolidone is 5 - 10:1, the concentration of the modified hexagonal boron nitride aqueous solution is 2 - 10 mg / mL, the ultrasonic time during the ultrasonic dispersion process is 10 - 30 min, and the conditions for magnetic stirring and heating are that the magnetic stirring speed is 500 - 600 rpm and the heating temperature is 60 - 100 °C.

[0040] In various embodiments of the present disclosure, preferably, the concentration of the silver nitrate solution is 15 - 30 mg / mL, the addition method is to inject it into the reaction system using a pipette, and the mass ratio of the modified hexagonal boron nitride to silver nitrate is 4 - 20:1.

[0041] In various embodiments of the present disclosure, when centrifuging and vacuum drying the mixed solution, preferably, the centrifugation speed is 2000 - 10000 rpm and the centrifugation time is 10 - 30 min; the vacuum drying temperature is 60 - 80 °C and the time is 8 - 16 h.

[0042] In various embodiments of the present disclosure, the preparation method of the aramid nanofiber composite material is as follows:

[0043] Step 1: Disperse aramid nanofibers in a dimethyl sulfoxide solution of potassium hydroxide to obtain an aramid nanofiber / dimethyl sulfoxide dispersion, and disperse it in deionized water to obtain an aramid nanofiber dispersion.

[0044] Step 2: After ultrasonic dispersing the hexagonal boron nitride supported silver nanoparticle hybrid filler in deionized water to prepare a dispersion liquid, mechanically mix it with the aramid nanofiber dispersion liquid to obtain a mixed system;

[0045] Step 3: Use the wet papermaking method to subject the mixed system to aqueous physical blending, vacuum-assisted filtration, and vacuum drying treatments to prepare an aramid nanofiber composite material.

[0046] In each embodiment of the present disclosure, preferably, the aramid nanofibers are aramid nanofibers cracked to a diameter of 1 - 100 nm, so as to obtain a stable aramid nanofiber / dimethyl sulfoxide dispersion liquid. The aramid nanofibers in it inherit the excellent mechanical properties, electrical insulation properties, and thermal stability of aramid fibers, and have a high specific surface area and large aspect ratio, and can be used as a polymer matrix for relatively ideal thermal conductive composite materials.

[0047] In each embodiment of the present disclosure, preferably, the concentration of potassium hydroxide in the dimethyl sulfoxide solution of potassium hydroxide is 1 - 5 g / L, and the volume ratio of dimethyl sulfoxide to deionized water is 10 - 50:1; preferably, the mass ratio of aramid nanofibers to potassium hydroxide is 1:0.5 - 2.5.

[0048] In each embodiment of the present disclosure, preferably, the aramid nanofibers are dispersed in the dimethyl sulfoxide solution of potassium hydroxide by stirring, the stirring temperature is 20 - 30 °C, the stirring rate is 500 - 800 r / min, and the reaction time is 2 - 8 h.

[0049] In each embodiment of the present disclosure, preferably, the volume ratio of the aramid nanofiber / dimethyl sulfoxide dispersion liquid to deionized water is 1:4 - 8, and the aramid nanofiber dispersion liquid is mixed by a high-speed shearer, the mixing rate is 8000 - 10000 rpm, and the mixing time is 1 - 5 min.

[0050] In each embodiment of the present disclosure, preferably, the time for ultrasonic dispersing the hexagonal boron nitride supported silver nanoparticle hybrid filler in deionized water is 30 min; the concentration of the deionized water dispersion liquid of the hexagonal boron nitride supported silver nanoparticle hybrid filler is 0.4 - 0.5 mg / mL.

[0051] In each embodiment of the present disclosure, preferably, the high-speed shearer is used for mechanical mixing to obtain the mixed system, the mixing rate is 12000 rpm, and the mixing time is 1 - 5 min.

[0052] In each embodiment of the present disclosure, preferably, during the wet papermaking process, the force of vacuum-assisted filtration is 0.5 - 0.8 MPa; the temperature of vacuum drying is 50 - 80 °C, and the time is 8 - 16 h.

[0053] In various embodiments of the present disclosure, preferably, the mass of the hexagonal boron nitride-supported silver nanoparticle hybrid filler accounts for 40-50 wt% of the total mass of the hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite.

[0054] The following are the preferred embodiments and comparative examples of the present disclosure.

[0055] Example 1

[0056] A method for preparing a hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite comprises the following steps:

[0057] Step 1: Add 0.5 g of h-BN powder (Dandong Chemical Research Institute) to 30 mL of a 30 mg / mL tannic acid aqueous solution, ultrasonically disperse for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain an h-BN dispersion liquid. Then transfer the h-BN dispersion liquid to a corundum ball milling tank, and add 100 g of zirconia grinding beads with a diameter of 10 mm and 100 g of zirconia grinding beads with a diameter of 5 mm. Ball mill at a rotation speed of 400 rpm for 12 h to obtain a mixed solution. After the ball milling reaction ends, centrifuge the mixed solution at 8000 rpm to obtain modified hexagonal boron nitride. Add 0.5 g of the modified hexagonal boron nitride and 0.1 g of a polyvinylpyrrolidone solution to 100 mL of deionized water, ultrasonically disperse for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a mixed dispersion liquid. Then heat to 80 °C under magnetic stirring at 600 rpm, inject 1 mL of a 25 mg / mL silver nitrate solution, stop stirring and heating after reacting for 5 min. After the reaction system cools to room temperature, centrifuge the mixed solution at 8000 rpm, and then vacuum dry the separated wet powder at 60 °C for 12 h to obtain a hexagonal boron nitride-supported silver nanoparticle hybrid filler;

[0058] Step 2: Mix 1.5 g of potassium hydroxide, 20 mL of deionized water and 480 mL of dimethyl sulfoxide to prepare a dimethyl sulfoxide solution of potassium hydroxide. Dissolve 1.0 g of aramid nanofibers in the dimethyl sulfoxide solution of potassium hydroxide, and magnetically stir at a rotation speed of 600 rpm at 25 °C for 10 h to obtain an aramid nanofiber / dimethyl sulfoxide solution with a concentration of 2 mg / mL. Take 15 mL of the aramid nanofiber / dimethyl sulfoxide solution, add 60 mL of deionized water and mix evenly to obtain an aramid nanofiber dispersion liquid with a concentration of 0.4 mg / mL.

[0059] Step 3: Add the 20 mg of the hexagonal boron nitride-supported silver nanoparticle hybrid filler obtained in Step 1 into deionized water, and ultrasonically disperse it for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a dispersion of the hexagonal boron nitride-supported silver nanoparticle hybrid filler. Mechanically mix it with the 75 mL of the aramid nanofiber dispersion obtained in Step 2 using a high-speed shear mixer at a rotational speed of 8000 rpm for 3 min to obtain a mixed system;

[0060] Step 4: Apply a force of 0.6 MPa to the mixed system for vacuum-assisted filtration to obtain a wet hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite material, and then vacuum-dry it at 60 °C for 12 h to obtain the hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite material. The content of the modified hexagonal boron nitride in the obtained hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite material is 40 wt%.

[0061] Example 2

[0062] Other steps of this example are the same as those of Example 1, except that the volume of the silver nitrate solution injected is 3 mL.

[0063] Example 3

[0064] Other steps of this example are the same as those of Example 1, except that the volume of the silver nitrate solution injected is 5 mL.

[0065] Example 4

[0066] Other steps of this example are the same as those of Example 1, except that the content of the hexagonal boron nitride-supported silver nanoparticle hybrid filler in the obtained hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite material is 50 wt%.

[0067] Example 5

[0068] Other steps of this example are the same as those of Example 1, except that the volume of the silver nitrate solution injected is 3 mL and the content of the hexagonal boron nitride-supported silver nanoparticle hybrid filler in the obtained hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite material is 50 wt%.

[0069] Example 6

[0070] Other steps of this example are the same as those of Example 1, except that the volume of the silver nitrate solution injected is 5 mL and the content of the hexagonal boron nitride-supported silver nanoparticle hybrid filler in the obtained hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite material is 50 wt%.

[0071] Example 7

[0072] The other steps of this embodiment are the same as those of Embodiment 1, except that the modifier aqueous solution is used, and the modifier is gallic acid.

[0073] Comparative Example 1

[0074] A method for preparing an aramid nanofiber paper-based material comprises the following steps:

[0075] Step 1: Mix 1.5 g of potassium hydroxide, 20 mL of deionized water, and 480 mL of dimethyl sulfoxide to prepare a dimethyl sulfoxide solution of potassium hydroxide. Take 1.0 g of aramid nanofibers and dissolve them in the dimethyl sulfoxide solution of potassium hydroxide. Magnetically stir at a speed of 600 rpm at 25 °C for 10 h to obtain an aramid nanofiber / dimethyl sulfoxide solution with a concentration of 2 mg / mL. Take 25 mL of the aramid nanofiber / dimethyl sulfoxide solution and add 100 mL of deionized water and mix evenly to obtain an aramid nanofiber dispersion with a concentration of 0.4 mg / mL.

[0076] Step 2: Perform vacuum-assisted filtration on the aramid nanofiber dispersion with a force of 0.6 MPa to obtain a wet aramid nanofiber paper-based material, and then vacuum dry it at 60 °C for 12 h to obtain the aramid nanofiber paper-based material.

[0077] Comparative Example 2

[0078] A method for preparing a modified hexagonal boron nitride / aramid nanofiber composite material comprises the following steps:

[0079] Step 1: Add 1 g of h-BN powder (Dandong Chemical Research Institute) to 30 mL of 30 mg / mL tannic acid aqueous solution and ultrasonically disperse for 30 min. The ultrasonic frequency is 40 kHz, and the ultrasonic power is 800 W to obtain an h-BN dispersion. Then transfer the h-BN dispersion to a corundum ball mill jar and add 100 g of zirconia grinding beads with a diameter of 10 mm and 100 g of zirconia grinding beads with a diameter of 5 mm; ball mill at a speed of 400 rpm for 12 h to obtain a mixed solution; after the ball milling reaction ends, centrifuge the mixed solution at 8000 rpm, and then vacuum dry the separated wet powder at 60 °C for 12 h to obtain modified hexagonal boron nitride;

[0080] Step 2: Mix 1.5 g of potassium hydroxide, 20 mL of deionized water, and 480 mL of dimethyl sulfoxide to prepare a dimethyl sulfoxide solution of potassium hydroxide. Take 1.0 g of aramid nanofibers and dissolve them in the dimethyl sulfoxide solution of potassium hydroxide. Magnetically stir at a speed of 600 rpm at 25 °C for 10 h to obtain an aramid nanofiber / dimethyl sulfoxide solution with a concentration of 2 mg / mL. Take 15 mL of the aramid nanofiber / dimethyl sulfoxide solution and add 60 mL of deionized water and mix evenly to obtain an aramid nanofiber dispersion with a concentration of 0.4 mg / mL.

[0081] Step 3: Add 20 mg of the modified hexagonal boron nitride obtained in Step 1 into deionized water, and ultrasonically disperse it for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a tannic acid-modified hexagonal boron nitride dispersion. Mechanically mix it with 75 mL of the aramid nanofiber dispersion obtained in Step 2 using a high-speed shear mixer at a rotation speed of 8000 rpm for 3 min to obtain a mixed system;

[0082] Step 4: Apply a force of 0.6 MPa to the mixed system for vacuum-assisted filtration to obtain a wet tannic acid-modified hexagonal boron nitride / aramid nanofiber composite material, and then vacuum-dry it at 60 °C for 12 h to obtain a tannic acid-modified hexagonal boron nitride / aramid nanofiber composite material. The content of the modified hexagonal boron nitride in the obtained tannic acid-modified hexagonal boron nitride / aramid nanofiber composite material is 40 wt%.

[0083] Comparative Example 3

[0084] Other steps of this example are the same as those of Comparative Example 2, except that the content of the modified hexagonal boron nitride in the obtained modified hexagonal boron nitride / aramid nanofiber composite material is 50 wt%.

[0085] Comparative Example 4

[0086] Other steps of this example are the same as those of Comparative Example 2, except that the modifier aqueous solution used has gallic acid as the modifier.

[0087] Comparative Example 5

[0088] A preparation method of a hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite material prepared using a strong reducing agent is as follows:

[0089] Step 1: Add 1 g of h-BN powder (Dandong Chemical Research Institute) into 30 mL of 30 mg / mL tannic acid aqueous solution, and ultrasonically disperse it for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain an h-BN dispersion. Then transfer the h-BN dispersion to a corundum ball milling tank, and add 100 g of zirconia grinding beads with a diameter of 10 mm and 100 g of zirconia grinding beads with a diameter of 5 mm. Ball mill at a rotation speed of 400 rpm for 12 h to obtain a mixed solution. After the ball milling reaction is completed, centrifuge the mixed solution at 8000 rpm to obtain modified hexagonal boron nitride. Add 0.5 g of modified hexagonal boron nitride and 0.1 g of polyvinylpyrrolidone solution into 100 mL of deionized water, then add 1 mL of sodium borohydride solution with a concentration of 5 mg / mL, and ultrasonically disperse it for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a mixed dispersion. Then, under an ice bath and magnetic stirring at 600 rpm, inject 1 mL of silver nitrate solution with a concentration of 25 mg / mL, stop stirring after reacting in the dark for 30 min. After the reaction system returns to room temperature, centrifuge the mixed solution at 8000 rpm, and then vacuum dry the separated wet powder at 60 °C for 12 h to obtain hexagonal boron nitride supported silver nanoparticle hybrid filler prepared using a strong reducing agent;

[0090] Step 2: Mix 1.5 g of potassium hydroxide, 20 mL of deionized water and 480 mL of dimethyl sulfoxide together to prepare a dimethyl sulfoxide solution of potassium hydroxide. Dissolve 1.0 g of aramid nanofibers in the dimethyl sulfoxide solution of potassium hydroxide, and magnetically stir at a rotation speed of 600 rpm at 25 °C for 10 h to obtain an aramid nanofiber / dimethyl sulfoxide solution with a concentration of 2 mg / mL. Take 15 mL of the aramid nanofiber / dimethyl sulfoxide solution, add 60 mL of deionized water and mix evenly to obtain an aramid nanofiber dispersion with a concentration of 0.4 mg / mL;

[0091] Step 3: Add 20 mg of the hexagonal boron nitride supported silver nanoparticle hybrid filler prepared using a strong reducing agent obtained in Step 1 into deionized water, and ultrasonically disperse it for 30 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W to obtain a dispersion of hexagonal boron nitride supported silver nanoparticle hybrid filler prepared using a strong reducing agent. Mechanically mix it with 75 mL of the aramid nanofiber dispersion obtained in Step 2 using a high-speed shearer at a rotation speed of 8000 rpm for 3 min to obtain a mixed system;

[0092] Step 4: Vacuum-assisted filtration of the mixed system is carried out with a force of 0.6 MPa to obtain a wet hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite prepared using a strong reducing agent, and then it is vacuum-dried at 60 °C for 12 h to obtain a hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite prepared using a strong reducing agent. The content of modified hexagonal boron nitride in the obtained hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite prepared using a strong reducing agent is 40 wt%.

[0093] Comparative Example 6

[0094] Other steps of this example are the same as those of Comparative Example 5, except that the content of the hexagonal boron nitride-supported silver nanoparticle hybrid filler prepared using a strong reducing agent in the obtained hexagonal boron nitride-supported silver nanoparticle hybrid filler / aramid nanofiber composite prepared using a strong reducing agent is 50 wt%.

[0095] The following corresponding tests are carried out on Examples 1-7 and Comparative Examples 1-6.

[0096] As Figure 1 shown, there are two characteristic peaks at 1373 cm-1 and 817 cm-1 corresponding to the B-N bond in the original boron nitride. In the modified hexagonal boron nitride after ball milling with tannic acid aqueous solution in Example 1 and the modified hexagonal boron nitride after ball milling with gallic acid aqueous solution in Example 7, in addition to the characteristic peaks of B-N, a characteristic peak of the C-O bond (1706 cm-1) belonging to catechol also appears. In the infrared spectra of the hexagonal boron nitride-supported silver nanoparticles prepared in Example 1 and Example 7, the characteristic peak of the C-O bond disappears, and instead, a characteristic absorption peak of the C=O bond (1630 cm-1) belonging to o-benzoquinone appears, which proves that catechol is oxidized to o-benzoquinone, achieving the purpose of reducing silver ions to silver nanoparticles.

[0097] As Figure 2 shown, for the hexagonal boron nitride-supported silver nanoparticle hybrid fillers of Examples 1, 2, 3, and 7, the silver nanoparticles can be effectively in-situ reduced on the surface of hexagonal boron nitride by the modifiers tannic acid and gallic acid containing catechol groups. The silver nanoparticles are uniformly dispersed on the surface of hexagonal boron nitride, with basically no agglomeration phenomenon, and the particle sizes are relatively uniform, without obvious large particles and plate-like particles. With the increase in the addition amount of silver nitrate solution, the loading amount of silver nanoparticles on the surface of hexagonal boron nitride also increases, fully proving that the present invention does not need to rely on a strong reducing agent, and the modified hexagonal boron nitride still has good ability to reduce silver nanoparticles, and the loading amount of silver nanoparticles on hexagonal boron nitride can be adjusted according to the requirements in the actual application process.

[0098] Figure 3The hexagonal boron nitride supported silver nanoparticle hybrid filler prepared using a strong reducing agent in Comparative Example 5 has a too strong reducing ability of the strong reducing agent, resulting in an excessively fast reduction rate. Not only does the preparation process require harsh reaction conditions such as ice bath and light avoidance to control the reaction rate, but it also causes uneven particle sizes of the silver nanoparticles, agglomeration on the surface of the hexagonal boron nitride, and the formation of irregularly shaped nanoplates. In addition, the binding between the silver nanoparticles and the hexagonal boron nitride is not tight, and some silver nanoparticles fall off from the surface of the hexagonal boron nitride when dispersed in ethanol to prepare an SEM sample on a silicon wafer substrate and adhere to the silicon wafer substrate. In contrast Figure 2 , for the hexagonal boron nitride supported silver nanoparticle hybrid fillers prepared in Examples 1, 2, 3, and 7 without using a strong reducing agent and only prepared using an organic modifier containing a catechol group, since the reducing agent of catechol is far less strong than strong reducing agents such as sodium borohydride, the slower reduction rate helps to load nanoparticles with uniform particle sizes on the silver nanoparticles, and there will be no hexagonal or triangular plate shapes. Moreover, the o-benzoquinone generated after the oxidation of catechol also helps the uniform adsorption of silver nanoparticles on the surface of the hexagonal boron nitride and reduces the generation of agglomeration.

[0099] To further characterize the thermal conductivity and mechanical properties of the hexagonal boron nitride supported silver nanoparticle hybrid filler / aramid nanofiber composites obtained in the above examples and comparative examples, the composites were tested according to the following method: 1. The in-plane thermal conductivity of the thermally conductive composite material and the aramid nanofiber paper-based material was measured respectively using the transient plane heat source method (Hotdisk); 2. The tensile strength of the thermally conductive composite material and the aramid nanofiber paper-based material was tested using a small load universal electronic testing machine to characterize the mechanical properties of the material. The test results are shown in Table 1.

[0100] Table 1 Test parameter table of aramid nanofiber composites in Examples 1-7 and Comparative Examples 1-6

[0101]

[0102] As can be seen from Table 1, the in-plane thermal conductivity of the hexagonal boron nitride supported silver nanoparticle hybrid filler / aramid nanofiber composites in Examples 1-7 is higher than that of the pure aramid nanofiber paper-based material in Comparative Example 1. Among them, the in-plane thermal conductivity of Example 6 reaches 5.00 W / mK, and the thermal conductivity improvement rate reaches 155%. This shows that the addition of the hexagonal boron nitride supported silver nanoparticle hybrid filler can significantly improve the thermal conductivity of the composite material. The tensile strength of the composites in Examples 1-7 has a certain degree of decrease compared with that in Comparative Example 1, but the lowest tensile strength is also 30.13 MPa, indicating that the composite material still has certain mechanical properties, and the attenuation of the mechanical properties is within a controllable range.

[0103] As can be seen from Table 1, the in-plane thermal conductivity of the hexagonal boron nitride loaded silver nanoparticle hybrid filler / aramid nanofiber composite materials in Examples 1-6 is higher than that of the modified hexagonal boron nitride / aramid nanofiber composite materials in Comparative Examples 2-3, and the highest thermal conductivity improvement rate is 11.77%. The in-plane thermal conductivity of the hexagonal boron nitride loaded silver nanoparticle hybrid filler / aramid nanofiber composite material in Example 7 is higher than that of the modified hexagonal boron nitride / aramid nanofiber composite material in Comparative Example 4. This shows that loading silver nanoparticles on hexagonal boron nitride to make a hybrid filler can effectively reduce the interfacial thermal resistance between the hexagonal boron nitride and the matrix, and improve the thermal conductivity of the composite material. It is noted that although the in-plane thermal conductivity of the composite material is improved to a certain extent after silver nanoparticles are loaded on the surface of hexagonal boron nitride, the improvement is not as high as expected. This is because the content of silver nanoparticles in the composite material is kept low as a whole, and the thermal conductivity of the composite material is mainly affected by the content of hexagonal boron nitride. When the content of hexagonal boron nitride remains basically unchanged, the improvement effect of silver nanoparticles is limited. In addition, the tensile strength of the composite materials of Examples 1-6 is compared with that of Comparative Examples 2-3, and the tensile strength of the composite material of Example 7 is compared with that of Comparative Example 4. This is because the introduction of silver nanoparticles may form stress concentration points in the composite material, making the material more prone to cracks and fractures when subjected to stress. However, despite the high loading of silver nanoparticles, the lowest tensile strength is 30.13MPa, which shows that the introduction of silver nanoparticles makes the attenuation of the mechanical properties of the composite material within a controllable range.

[0104] It can be seen from Table 1 that the in-plane thermal conductivity and tensile strength of the hexagonal boron nitride loaded silver nanoparticle hybrid filler / aramid nanofiber composite materials in Examples 1-6 are not much different from the in-plane thermal conductivity and tensile strength of the hexagonal boron nitride loaded silver nanoparticle hybrid filler / aramid nanofiber composite materials prepared using a strong reducing agent in Comparative Examples 5-6, and Examples 1-6 are slightly higher than Comparative Examples 5-6, which shows that when preparing hexagonal boron nitride loaded silver nanoparticle hybrid fillers, no strong reducing agent is used, and only a modifier containing a catechol group can still achieve the target thermal conductivity and mechanical properties of the composite material.

[0105] As can be seen from Table 1, the thermal conductivity and mechanical properties of the hexagonal boron nitride loaded silver nanoparticle hybrid filler / aramid nanofiber composite materials prepared in Example 1 and Example 7 are not much different, which shows that in the preparation process, different modifiers containing catechol groups have similar effects in enhancing the interaction between the filler and the matrix and promoting the formation and loading of silver nanoparticles. Therefore, in practical applications, tannic acid and gallic acid can replace each other, providing more selection flexibility for the preparation of composite materials.

[0106] In this application, a modifier is used to ball-mill modify hexagonal boron nitride thermal conductive filler to obtain modified hexagonal boron nitride, and then in-situ reduction is carried out with silver nitrate to obtain a hybrid filler with silver nanoparticles loaded on the surface of hexagonal boron nitride. The hybrid filler can play a bridging role between the polymer matrix and the thermal conductive filler, thereby optimizing the interface between the matrix and the filler. While improving the thermal conductivity of the composite material, it can also keep the composite material having certain mechanical properties. At the same time, the preparation method of this application does not need to use strong reducing agents, simplifies the preparation process of the hybrid filler of hexagonal boron nitride loaded with silver nanoparticles, reduces the cost, is convenient to operate, environmentally friendly, and easy to prepare on a large scale.

[0107] It can be understood that the above-mentioned various method embodiments mentioned in this disclosure can be combined with each other to form an embodiment after combination without violating the principle logic. Due to space limitations, this disclosure will not elaborate further. The above has described the embodiments of this disclosure. The above description is exemplary and not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes are obvious to those of ordinary skill in the art in the technical field without departing from the scope and spirit of the described embodiments. The choice of terms used herein is intended to best explain the principles of the embodiments, practical applications or technical improvements to the technologies in the market, or to enable other ordinary skill in the art in the technical field to understand the embodiments disclosed herein.

Claims

1. A hexagonal boron nitride-loaded silver nanoparticle hybrid filler, characterized in that: The preparation method of the filler comprises: After the hexagonal boron nitride is modified by an organic substance containing a catechol group, polyvinyl pyrrolidone is used as a protective agent, and silver nanoparticles are loaded on the surface of the hexagonal boron nitride by in-situ reduction of silver nitrate, thereby obtaining a hexagonal boron nitride-loaded silver nanoparticle hybrid filler.

2. The hexagonal boron nitride-supported silver nanoparticle hybrid filler according to claim 1, characterized in that: The method comprises: modifying hexagonal boron nitride with an organic substance containing a catechol group, using polyvinyl pyrrolidone as a protective agent, reducing silver nitrate, and loading silver nanoparticles on the surface of hexagonal boron nitride to obtain a hybrid filler of hexagonal boron nitride loaded with silver nanoparticles, comprising: An organic matter containing a catechol group is used as a modifier, and a liquid phase ball milling is performed on hexagonal boron nitride using an aqueous solution of the modifier. The modified hexagonal boron nitride obtained by centrifugal separation is then dispersed again in deionized water to prepare a modified hexagonal boron nitride aqueous solution. Polyvinyl pyrrolidone is added and ultrasonically dispersed uniformly. The aqueous solution is reacted with a silver nitrate solution under magnetic stirring and heating conditions, and a mixed solution is obtained by in-situ reduction and cooled to room temperature. The mixed solution is then centrifuged and vacuum dried to obtain the hexagonal boron nitride-loaded silver nanoparticle hybrid filler.

3. The hexagonal boron nitride-supported silver nanoparticle hybrid filler according to claim 2, characterized in that: The concentration of the modifier aqueous solution is 20-50 mg / mL, and the dispersion concentration of the hexagonal boron nitride powder in the modifier aqueous solution is 16.67-33.33 mg / mL.

4. The hexagonal boron nitride-supported silver nanoparticle hybrid filler according to claim 3, characterized in that: The mass ratio of modified hexagonal boron nitride to silver nitrate is 4 to 20:

1.

5. An aramid nanofiber composite material, characterized in that: include: The hexagonal boron nitride-loaded silver nanoparticle hybrid filler according to any one of claims 1 to 4.

6. The aramid nanofiber composite material according to claim 5, characterized in that: The hexagonal boron nitride loaded silver nanoparticle hybrid filler accounts for 40-50 wt% of the total mass of the aramid nanofiber composite material.

7. The method for preparing the aramid nanofiber composite material according to claim 5 or 6, characterized in that: include: Dispersing aramid nanofibers in a potassium hydroxide solution of dimethyl sulfoxide to obtain an aramid nanofiber / dimethyl sulfoxide dispersion, and dispersing the aramid nanofiber / dimethyl sulfoxide dispersion in deionized water to obtain an aramid nanofiber dispersion; The prepared deionized water dispersion of hexagonal boron nitride-loaded silver nanoparticle hybrid filler is mixed with the aramid nanofiber dispersion to obtain a mixed system; The mixed system is subjected to water phase physical blending, vacuum-assisted filtration and vacuum drying by a wet papermaking method to prepare the aramid nanofiber composite material.

8. The method for preparing the aramid nanofiber composite material according to claim 7, characterized in that: The mass ratio of the aramid nanofiber to potassium hydroxide is 1:0.5-2.5; the concentration of potassium hydroxide in the dimethyl sulfoxide solution of potassium hydroxide is 1-5 g / L, and the volume ratio of dimethyl sulfoxide to deionized water is 10-50:

1.

9. The method for preparing the aramid nanofiber composite material according to claim 8, characterized in that: The aramid nanofibers are dispersed in the potassium hydroxide dimethyl sulfoxide solution by stirring at a temperature of 20 to 30° C., at a stirring rate of 500 to 800 r / min, for a time of 2 to 8 hours; and / or The concentration of the deionized water dispersion of the hexagonal boron nitride-loaded silver nanoparticle hybrid filler is 0.4-0.5 mg / mL.

10. The method for preparing the aramid nanofiber composite material according to claim 9, characterized in that: The force of the vacuum-assisted filtration is 0.5-0.8 MPa; the temperature of the vacuum drying is 50-80° C., and the time is 8-16 hours.

Citation Information

Patent Citations

  • BNNs (at) Ag hybrid filler, nano-reinforced filler with different dimensions, self-lubricating fabric liner material, preparation and application of BNNs (at) Ag hybrid filler and self-lubricating fabric liner material

    CN117026625A

  • High-thermal-conductivity aramid fiber composite insulation paper for electrical equipment, preparation method and application of high-thermal-conductivity aramid fiber composite insulation paper

    CN118563588A

  • Phase-change heat-conducting composite material with core-sheath structure and coaxial DIW printing preparation method of phase-change heat-conducting composite material

    CN119529770A

  • Preparation method of silver nanowire based on phenolic compound and silver nanowire

    CN119839302A